Lessons learned from a peer-supported diabetes education program in two dissimilar Mayan communities - Castillo-Hernandez, Karen G.; Espinosa, Alan; Molina-Segui, Fernanda; Ayuso-Peraza, Giselle; Mena-Macossay, Leticia; Mendez-Dominguez, Nina; Bastarrachea, Raúl A.; Laviada-Molina, Hugo (Frontiers in Endocrinology, 2024)
Background A steady rise in type 2 diabetes (T2D) in Mexico over the last 30 years has led to 11.5 million Mexicans being affected by this condition. There is an urgent need to develop interventions to prevent complications of T2D. Diabetes self-management education is the cornerstone of promoting self-care. Among all educational strategies, peer support has shown to be an effective method to encourage ongoing self-management. However, customization of interventions for distinct communities is imperative, as failure to do so can hinder the intervention’s effectiveness. Methods We implemented a two-year prospective randomized controlled community-based trial in Conkal, a Mayan community from Yucatan, Mexico. The intervention consisted of receiving either a culturally sensitive peer support on top of a diabetes self-management education group (PLG); or a diabetes self-management education group only (EOG; control group). The primary outcome was changes in glycated hemoglobin, while secondary outcomes encompassed changes in systolic and diastolic blood pressure, body mass index, and diabetes self-care practices. Data collection was performed at baseline and every four months during the study period. Discussion Our experiences have highlighted the significance of peer-leader support in cultivating diabetes self-care skills, particularly within smaller, underserved communities characterized by strong social and cultural ties. However, when applied in larger or suburban settings, selecting peer leaders should be meticulous, considering sectorization within specific neighborhoods to foster a sense of belonging and familiarity among natural community clusters. In larger settlemnts, factors such as transportation challenges, time limitations, caregiving obligations, limited venue access, and changes in session locations can drive program discontinuation. Additionally, individuals with lower educational attainment are more susceptible to abandonment. Notably, those with lower education, uncontrolled diabetes, and extended diabetes duration exhibit a greater potential for improving glycemic control than their counterparts. Clinical registration https://www.isrctn.com/ISRCTN96897082.